Motivation and identity among European and Brazilian elite student-athletes: a Bayesian multilevel regression and poststratification analysis - Gonçalves, Carlos E.; Carvalho, Humberto M.; Fernandes, Ana; Éloi, Serge; Quinaud, Ricardo T.; Rama, Luis M. (Frontiers in Sports and Active Living, 2025)
IntroductionThe global dimension of elite sport enrolls a vast number of student-athletes and universities around the world. However, the majority of higher education institutions do not share the same vision and policies about education and elite sport. Hence, comparative studies are needed. The goal of the present study was to use Multilevel Regression with Poststratification to estimate variation between Brazilian and European university student-athletes’ motivation toward sports and academics, and two dimensions of identity, affectivity and social identity.Methods508 student-athletes (311 Brazilian, competing at the national university games; 197 European, competing at the European University Games) participated in the study and answered to two questionnaires used in cross-cultural research: SAMSAQ, for academic and sport motivation, and BIMS, for social identity and emotions.ResultsFor all the variables our estimations showed significant differences between Brazilian and European athletes, with the former expressing higher scores in all dimensions of motivation and identity.DiscussionThe findings suggest that the macro-effect of the organizational and cultural context is the most important source of influence on athletes’ motivation and identity, which appears to be more significant in Brazil. Cultural nuances among European countries and Brazilian states seem to have little impact on the athletes’ responses. It is necessary to move on from an ethnographic stance and assume methodological sophistication as a way to assimilate a body of knowledge that can be subject of comparison and interpretation. Educators need to compare and see what works at a global level, because thousands of elite athletes are enrolled in higher education and feed national and international competitions with their commitment and quality. Our findings highlight the need for policymakers and educational institutions to develop tailored support systems that acknowledge the cultural and organizational differences impacting student-athlete motivation and identity. Implementing flexible academic programs, fostering supportive athletic environments, and promoting dual career pathways are crucial for optimizing the student-athlete experience globally.